Prolonged periorbicular edema after injection of hyaluronic acid for nasojugal groove correction (2019)
The injection of hyaluronic acid (HA), a naturally occurring biopolymer, is a common cosmetic procedure. Despite their efficacy and growing adaptation by the medical community, HA fillers occasionally give rise to adverse events. Adverse events from HA fillers range from temporary, such as edema and erythema, to more longterm effects, including granulomas or, in rare cases, sequelae from vascular occlusion. Here, we present a case of a 61yearold Caucasian woman with prolonged infraorbital hollow edema after injection of HA filler for nasojugal groove correction. We review the anatomy of the nasojugal area and differing injection techniques as a possible explanation for the development of prolonged edema. Similarly, the rheological properties of the specific hyaluronic acid used during this procedure might be crucial in the development of this complication. © 2019 Matrix Medical Communications. All rights reserved.